How few and far between? Examining the effects of probe rate on self-reported mind wandering - Seli, Paul; Carriere, Jonathan S.; Levene, Merrick; Smilek, Dan (Frontiers in Psychology, 2013)
We examined whether the temporal rate at which thought probes are presented affects the likelihood that people will report periods of mind wandering. To evaluate this possibility, we had participants complete a sustained-attention task (the Metronome Response Task; MRT) during which we intermittently presented thought probes. Critically, we varied the average time between probes (i.e., probe rate) across participants, allowing us to examine the relation between probe rate and mind-wandering rate. We observed a positive relation between these variables, indicating that people are more likely to report mind wandering as the time between probes increases. We discuss the methodological implications of this finding in the context of the mind-wandering literature, and suggest that researchers include a range of probe rates in future work to provide more insight into this methodological issue.